Comparative antiseizure medications of adjunctive treatment for children with drug-resistant focal-onset seizures: A systematic review and network meta-analysis - Zhang, Lanlan; Li, Yuehong; Wang, Weikai; Wang, Chengzhong (Frontiers in Pharmacology, 2022)
Purpose: In this study, we intended to compare and rank the efficacy and acceptability of antiseizure medications (ASMs) for adjunctive treatment of children with drug-resistant focal-onset seizures. Method: We conducted a computerized search of PubMed, EMBASE, Cochrane Library, Web of Science, and Google Scholar to identify eligible randomized controlled trials (RCTs) published before May 31, 2022. We included studies evaluating the efficacy and tolerability of ASMs for children with drug-resistant focal‑onset seizures. The efficacy and safety were reported in terms of responder and dropout rate along with serious adverse events, the outcomes were ranked with the surface under the cumulative ranking curve (SUCRA). Results: A total of 14 studies (16 trials) with 2464 patients were included, involving 10 active ASMs. For the primary endpoint of at least 50% reduction in focal-onset seizures, the SUCRA ranking suggested that lamotrigine and levetiracetam were more effective as compared with other ASMs; moreover, levetiracetam had the highest probability of rank first for achieving seizure freedom. Concerning tolerability, oxcarbazepine and eslicarbazepine acetate were associated with higher dropout rates relative to other ASMs and placebo, and topiramate was associated with higher occurrence of side effects. No significant differences were found between active ASMs concerning dropout for side effects. Conclusions: According to the SUCRA ranking, lamotrigine, levetiracetam, and oxcarbazepine were more efficacious than other active ASMs in terms of responder rate. Concerning tolerability, oxcarbazepine was more likely to lead to dropout and topiramate was associated with higher occurrence of side effects.